Social care work and social work in Ireland: A comparative analysis of standards of proficiency - Flynn, Susan (My University, 2024)
This article provides a timely intervention to debates and scholarship about the professional regulation of social work and social care. In Ireland, the recent commencement of the statutory regulation of social care by CORU – Ireland’s multi-professional health regulator – offers a watershed opportunity for learning. Social work has been separately regulated by CORU for over a decade, while the social care work register opened in November 2023. We conduct a comparative content analysis of the standards of proficiency for social work and for social care work. Albeit with different historical origins, regulation has now provided these professions with distinctive, as well as shared professional ‘benchmarks’, that may shape the trajectories of their future roles and training. We consider the approach CORU takes to regulation, in terms of the standards and how these differentiate or align the two professions. The novel contribution of the paper lies in its key findings. Namely, that: the format of the standards of proficiency framework itself warrants further consideration; insufficient attention is paid to empathy and emotions across standards; there is an absence of a considered approach to the influence of socio-economic factors on practice; there are variations in the emphasis placed on relational versus socio-political dimensions in practice; and finally, there are differences in the importance paid to ‘critical understanding’ across the standards. These areas particularly illuminate how CORU frames and interprets the nature of both professions. It is concluded that the standards of proficiency for both social care work and social work have much shared terrain, interspersed with infrequent but striking differences, indicative of the many commonalities and overlap in occupational spheres for both professions.
Keywords: social care work, social work, comparative analysis, professional regulation, standards of proficiency